ON THE DATE OF GREGORY OF NYSSA'S FIRST HOMILIES ON THE FORTY MARTYRS OF SEBASTE (IA AND IB) - Leemans, Johan (The journal of theological studies, 2001)
JOHAN LEEMANS; ON THE DATE OF GREGORY OF NYSSA'S FIRST HOMILIES ON THE FORTY MARTYRS OF SEBASTE (IA AND IB), The Journal of Theological Studies, Volume 52, Issu